The Impact of Cyclical Factors on the U. S. Balance of Payments - Greene, Joshua; Kandil, Magda (Washington, D.C. : International Monetary Fund, 2002)
Real GDP growth and real effective exchange rate (REER) appreciation appear cointegrated with the current and financial accounts of the U.S. balance of payments. On this basis, we estimate reduced form equations showing that expected changes and shocks to real GDP, the REER, energy prices, and growth in emerging market economies and other industrial countries explain much of the short-term variation in the U.S. current account balance, with the balance worsening as real GDP, energy prices, and the REER increase. In addition, foreign direct investment rises with real growth, while stock market prices affect the composition of capital inflows.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet